Nilai-Nilai Pendidikan Karakter dalam Surah Yusuf: Pendekatan Integratif dalam Pembentukan Akhlak Generasi Muda - Burhanuddin (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2024)
Character education is a fundamental aspect in the development of one's personality and morals. Surah Yusuf, one of the surahs in the Qur'an, contains educational values ​​that are very relevant to forming noble morals. This study aims to analyze the values ​​of character education contained in Surah Yusuf and explore ways in which these values ​​can be applied in educating a generation with character and high morals. This study uses a qualitative method with an integrative approach that combines the study of interpretation, pedagogy, and character values. The results of the study show that Surah Yusuf contains character values ​​such as honesty, patience, determination, and justice that can be integrated into the educational process to form a generation with strong character and high morals.